An enigmatic Rhachotropis (Crustacea: Amphipoda: Eusiridae) from New Zealand - Lörz, Anne-Nina (Zootaxa, 2015)
The eusirid genus Rhachotropis S.I. Smith, 1883 has a worldwide distribution and the largest bathymetric range known from any amphipod genus. A large, charismatic, colourful species was collected below 800 m at two sites 1000 km apart on the southern Kermadec Ridge and on the Chatham Rise in the south-western Pacific off eastern New Zealand. The new species, Rhachotropis oweni is described, increasing the total number of Rhachotropis to 61 species worldwide, including six species from New Zealand waters.